Enzymatic Synthesis of 3'-5', 3'-5' Cyclic Dinucleotides, Their Binding Properties to the Stimulator of Interferon Genes Adaptor Protein, and Structure/Activity Correlations - Novotná, Barbora; Holá, Lucie; Staś, Monika; Gutten, Ondrej; Smola, Miroslav; Zavřel, Martin; Vavřina, Zdeněk; Buděšínský, Miloš; Liboska, Radek; Chevrier, Florian; Dobiaš, Juraj; Boura, Evzen; et al. (Biochemistry, 2021)
The 3'-5', 3'-5' cyclic dinucleotides (3'3'CDNs) are bacterial second messengers that can also bind to the stimulator of interferon genes (STING) adaptor protein in vertebrates and activate the host innate immunity. Here, we profiled the substrate specificity of four bacterial dinucleotide synthases from Vibrio cholerae (DncV), Bacillus thuringiensis (btDisA), Escherichia coli (dgcZ), and Thermotoga maritima (tDGC) using a library of 33 nucleoside-5'-triphosphate analogues and then employed these enzymes to synthesize 24 3'3'CDNs. The STING affinity of CDNs was evaluated in cell-based and biochemical assays, and their ability to induce cytokines was determined by employing human peripheral blood mononuclear cells. Interestingly, the prepared heterodimeric 3'3'CDNs bound to the STING much better than their homodimeric counterparts and showed similar or better potency than bacterial 3'3'CDNs. We also rationalized the experimental findings by in-depth STING-CDN structure-activity correlations by dissecting computed interaction free energies into a set of well-defined and intuitive terms. To this aim, we employed state-of-the-art methods of computational chemistry, such as quantum mechanics/molecular mechanics (QM/MM) calculations, and complemented the computed results with the {STING:3'3'c-di-ara-AMP} X-ray crystallographic structure. QM/MM identified three outliers (mostly homodimers) for which we have no clear explanation of their impaired binding with respect to their heterodimeric counterparts, whereas the R2 = 0.7 correlation between the computed ΔG'int_rel and experimental ΔTm's for the remaining ligands has been very encouraging.
Keywords: přirozená imunita; Cytokines; Escherichia coli; nukleotidy; Substrate Specificity; Quantum Theory; Thermotoga maritima; cytokiny; Structure-Activity Relationship; Vibrio cholerae; Leukocytes, Mononuclear; lidé; membránové proteiny; krystalografie rentgenová; Nucleotides; Bacillus thuringiensis; Immunity, Innate; vztahy mezi strukturou a aktivitou; Membrane Proteins; Crystallography, X-Ray; substrátová specifita; kvantová teorie; leukocyty mononukleární; Humans